Ecological aspects of water impoundment in the tropics - Goldman, Charles R. (Revista de Biología Tropical, 1976)
Recognition of the potentially harmful effects of water development in the tropics has led to increasing efforts to assess the environmental impact of such projects prior to construction. Decisions regarding the development or non-development of water resources must be based on sound investigation of both the long-and short-term effects of reservoir construction and operation. The environmental effects of water impoundment vary greatly with the characteristics of the region as well as the type of reservoir to be constructed (area and depth of reservoir, ratio of water inflow to storage). Of major concern are the reduction of reservoir capacity as sediments accumulate behind the dam and the loss of these sediments to downstream agriculture and fisheries. The potential impact of altered flow regimes, siltation, reduction in beach formation and nutrient enrichment at the mouths of rivers, and the possibility of saltwater encroachment should receive careful study. A thorough description of the plants and animals to be affected by inundation should be made to -determine the possible loss of rare OI key organisms as well as the potential development of "nuisance species". Included in this survey should be a detailed study of existing fish and the potential for commercial fishery development in the proposed reservoir. Consideration should be given to vegetation removal in the reservoir basin prior to inundation, since decaying vegetation can result in deoxygenation, formation of hydrogen sulfide, possible development of suitable habitats for undesirable species and snagging of fish nets. Sanitation and land use practices as well as erosion in the watershed surrounding the reservoir must be controlled to prevent accelerated eutrophication caused by increased nutrient loading. Inundation in tropical areas can have serious sociological and human health implications including the increase of diseases, e.g., malaria, schistosomiasis, anchocerciasis, and dysentery, and the probable resettlement and alteration of land use practices. Census information and surveys concerning land use, housing and health standards and the social and economic structure of the community to be affected must be evaluated in order to anticipate and avoid potential problems. The archaeologic, historic, scenic and recreational value of the site to be inundated must also be considered. Studies of the El Cajón site on the Sula River in Honduras and the Purari River Project in Papua, New Guinea, are utilized as examples in this report.